SETIA Health Education Set Enhances Knowledge, Attitude, and Parenting Self-Efficacy Score in Postpartum Adolescent Mothers. (30th November 2017) - Setiawati, Nina; Setyowati,; Budiati, Tri
ABSTRACT: The lack of readiness in assuming the role of a mother causes many adolescent mothers to decide not to breastfeed their babies. This study was conducted to assess the effect of the SETIA health education set on adolescent mothers' knowledge, attitude, and parenting self-efficacy score. This quasi-experimental pre-test–post-test with control group study was conducted on 66 adolescent mothers, 33 participants in each group. Data collecting used knowledge and attitude questionnaires and the Parenting Self-Efficacy Scale (PSES). This study revealed that there was a significant difference before and after intervention in knowledge, attitude, and PSE score on postpartum adolescent mothers ( p  = .045; p  = .013; p  = .001 respectively). There was an increase in knowledge ≥ 20%, attitude ≥10%, parental self-efficacy ≥ 10%, and a difference between control and intervention group ( p  = .001 with 95% CI: 3.587–44.876, p  = .001 with 95% CI: 4.954–56.397, p  = .001 respectively). Logistic regression analysis found that postpartum adolescent mothers who receive SETIA are 12.687 times more likely to have better knowledge after being controlled for mother's age and education and 0.248 times more likely to have a higher PSES score after being controlled for mother's age, education, and husband's work status than their counterpart. This study recommends the use of the SETIA health education set to provide postpartum education to adolescent mothers.